The Influence of Education on the Human Development Index (Ipm) In Makassar City - Jam'an, Andi; Warda, Warda; Wulandari, Syarifah As Zahrah (Jurnal Ekonomi Balance, 2024)
This research aims to find out how much influence education has on the Human Development Index (HDI) in Makassar City. The research carried out was a type of quantitative research, using secondary data related to education and HDI in Makassar City during the 2012-2022 period. The research results show that education has a positive and significant influence on HDI in Makassar City. This is proven through the results of data processing which shows the education variable coefficient is 3.586 with a significance value of 0.000 which is smaller than 0.05 (0.000 < 0.05). In other words, education significantly influences the increase in HDI in Makassar City. These findings emphasize the importance of efforts to improve the education sector as one of the main strategies for improving the quality of life and welfare of the people in Makassar City. Thus, the government and stakeholders are expected to continue to prioritize investment in the education sector to encourage better development in the Human Development Index in the region